2011
DOI: 10.1371/journal.pgen.1002434
|View full text |Cite
|
Sign up to set email alerts
|

The RNA Silencing Enzyme RNA Polymerase V Is Required for Plant Immunity

Abstract: RNA–directed DNA methylation (RdDM) is an epigenetic control mechanism driven by small interfering RNAs (siRNAs) that influence gene function. In plants, little is known of the involvement of the RdDM pathway in regulating traits related to immune responses. In a genetic screen designed to reveal factors regulating immunity in Arabidopsis thaliana, we identified NRPD2 as the OVEREXPRESSOR OF CATIONIC PEROXIDASE 1 (OCP1). NRPD2 encodes the second largest subunit of the plant-specific RNA Polymerases IV and V (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
181
2
20

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(218 citation statements)
references
References 48 publications
15
181
2
20
Order By: Relevance
“…Mutations in several components of the RNA-directed DNA methylation pathway have been shown to alter immune responses to Pst DC3000. While mutations in AGRONAUTE4 (AGO4) compromise resistance to Pst DC3000 (Agorio and Vera, 2007), mutations in NRPE1 and NRPD2, which encode the largest subunit of the RNAP V complex and second largest subunit of the RNAP IV and V complexes, respectively (Law and Jacobsen, 2010), enhance resistance to this pathogen (López et al, 2011). The DNA methylation mutants met1-3 and ddc (drm1-2 drm2-2 cmt3-11), which are deficient in CG maintenance methylation and non-CG maintenance/de novo methylation, respectively (Saze et al, 2003;Chan et al, 2006;Penterman et al, 2007a), are highly resistant to Pst DC3000 (Dowen et al, 2012;Luna et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in several components of the RNA-directed DNA methylation pathway have been shown to alter immune responses to Pst DC3000. While mutations in AGRONAUTE4 (AGO4) compromise resistance to Pst DC3000 (Agorio and Vera, 2007), mutations in NRPE1 and NRPD2, which encode the largest subunit of the RNAP V complex and second largest subunit of the RNAP IV and V complexes, respectively (Law and Jacobsen, 2010), enhance resistance to this pathogen (López et al, 2011). The DNA methylation mutants met1-3 and ddc (drm1-2 drm2-2 cmt3-11), which are deficient in CG maintenance methylation and non-CG maintenance/de novo methylation, respectively (Saze et al, 2003;Chan et al, 2006;Penterman et al, 2007a), are highly resistant to Pst DC3000 (Dowen et al, 2012;Luna et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The DNA methylation mutants met1-3 and ddc (drm1-2 drm2-2 cmt3-11), which are deficient in CG maintenance methylation and non-CG maintenance/de novo methylation, respectively (Saze et al, 2003;Chan et al, 2006;Penterman et al, 2007a), are highly resistant to Pst DC3000 (Dowen et al, 2012;Luna et al, 2012). As AGO4 might play some unknown functions independent of the RNA-directed DNA methylation pathway (López et al, 2011), it has been proposed that DNA methylation represses immune responses to Pst DC3000 in the absence of the pathogen (Dowen et al, 2012). However, we found that the DNA demethylase triple mutant rdd (ros1-3 dml2-1 dml3-1), which contains genome-wide DNA hypermethylation (Penterman et al, 2007b;Lister et al, 2008), also exhibits constitutively elevated resistance to bacterial pathogens (see Supplemental Figure 8 online).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of a number of pathogen-responsive genes is up-regulated in mutants defective in DNA methylation (met1 and ddc1 [a drm1, drm2 and cmt3 triple mutant] mutants; Dowen et al, 2012). López et al (2011) reported that mutants defective in RNA POLYMERASE V, which is involved in DNA methylation through the RdDM pathway, show an up-regulation of SA-responsive genes and enhanced resistance toward Pseudomonas syringae. In rice, hypomethylation by treatment with the demethylating agent 5-azadeoxycytidine causes increased resistance to virulent strains of the bacterium Xanthomonas spp.…”
Section: Altered Metabolic Pathways In Hybridsmentioning
confidence: 99%
“…There is also evidence in Arabidopsis that Pol IV and Pol V activity can be uncoupled (Wierzbicki et al 2008(Wierzbicki et al , 2012Pontes et al 2009;Lopez et al 2011) and that Pol II-and Pol V-occupied sites are frequently found in close proximity to one another (Wierzbicki et al 2012). Therefore, it is feasible that, in the absence of Pol V, Pol II might be positioned to compensate for this activity.…”
Section: Discussionmentioning
confidence: 99%